Twenty-five-year changing pattern of gonococcal antimicrobial susceptibility in Shanghai: surveillance and its impact on treatment guidelines - Gu, Wei-Ming; Chen, Yue; Yang, Yang; Wu, Lei; Hu, Wei-Zhong; Jin, Yue-Lan (Université d'Ottawa | University of Ottawa, 2014)
Abstract Background Antimicrobial resistance of Neisseria gonorrhoeae is a serious health problem in China. Gonococcal antimicrobial susceptibility has been monitored in Shanghai since 1988. In this study, we examined the changing pattern of gonococcal antimicrobial susceptibility based on data from N. gonorrhoeae isolates collected over the past 25 years. Methods Approximately 100–200 isolates each year (1988–2013) were tested for their susceptibility to penicillin (PEN), tetracycline (TET), ciprofloxacin (CIP), ceftriaxone (CRO) and spectinomycin (SPT), using the agar dilution method. Plasmid-mediated N. gonorrhoeae antimicrobial resistance, comprising penicillinase-producing N. gonorrhoeae (presumed PPNG) and high-level tetracycline resistance N. gonorrhoeae (presumed TRNG), were also determined. Breakpoints for susceptibilities followed those described by the Clinical and Laboratory Standard Institute and the European Committee on Antimicrobial Susceptibility Testing. Results A high proportion of isolates were resistant to PEN, TET and CIP, ranging from less than 20% at the beginning of the survey, increasing in the late 1990s and reaching over 90% in recent years. The proportion of isolates exhibiting plasmid-mediated resistance exceeded 38% for presumed PPNG and 20% for presumed TRNG in recent years. The proportion of CRO nonsusceptible isolates (MIC ≥ 0.125 mg/L) ranged from 7% to 13% in most of the study years. Almost all isolates were susceptible to SPT. The SPT MIC90 was 16–32 mg/L for 2008–2013. The proportion of CRO nonsusceptible-associated multiple-drug-resistant (MDR) isolates was over 5% in most of the study years. Conclusions N. gonorrhoeae isolates in Shanghai were resistant to PEN, TET and CIP. Furthermore, CRO nonsusceptible and MDR isolates were prevalent. N. gonorrhoeae isolates were also found to be susceptible to SPT. It is recommended that the CRO dose be increased from currently recommended 250 mg to 500 mg and that SPT be an alternative in treating urogenital gonorrhea. Our findings highlight the importance of both regional and national surveillance programs for the prompt modification of treatment guidelines, vital in responding to the changing pattern of gonococcal antimicrobial susceptibility.